Perception of Corruption and Public Support for Redistribution in Latin America - Esther Hauk; Mónica Oviedo; Xavier Ramos (Institute of Labor Economics (IZA), 2017)
This paper studies the relationship between people's beliefs about the quality of their institutions, as measured by corruption perceptions, and preferences for redistribution in Latin America. Our empirical study is guided by a theoretical model which introduces taxes into Foellmi and Oechslin's (2007) general equilibrium model of non-collusive corruption. In this model perceived corruption influences people's preferences for redistribution through two channels. On the one hand it undermines trust in government, which reduces people's support for redistribution. On the other hand, more corruption decreases own wealth relative to average wealth of below-average-wealth individuals leading to a higher demand for redistribution. Thus, the effect of perceived corruption on redistribution cannot be signed a priori. Our novel empirical findings for Latin America suggest that perceiving corruption in the public sector increases people's support for redistribution. Although the positive channel dominates in the data, we also and evidence for the negative channel from corruption to demand for redistribution via reduced trust.
Keywords: D31; D63; H1; H2; P16; 330; preference for redistribution; perception of corruption; political trust; bribery; Latin America